Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Saving Behavior Mahasiswa di Universitas Teuku Umar - Ulva Widayanti; Fitria Mandaraira; Tamitha Intassar Husen (Indo Publishing, 2026)
This study aims to analyze the effect of financial literacy and financial inclusion on the saving behavior of students at Teuku Umar University. This study employed a quantitative approach with an associative research design. The population consisted of 5,520 active students at Teuku Umar University, with a sample of 382 respondents selected using the proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS version 4.1.1.4. The results indicate that financial literacy has no significant effect on students' saving behavior (t-statistics = 1.545; p-value = 0.123), whereas financial inclusion has a positive and significant effect on students' saving behavior (t-statistics = 10.102; p-value = 0.000). The Adjusted R Square value of 0.211 indicates that financial literacy and financial inclusion jointly explain 21.1% of the variance in students' saving behavior, while the remaining 78.9% is explained by other variables outside the research model. This study concludes that financial inclusion is a more dominant factor influencing students' saving behavior than financial literacy.